(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The article defines a concept of synesthesia on the ground of modern outlooks about the role of intersensory associations in the minds of native speakers, it is made attempt in the identification of its role in the folklore text. It is given a characteristic of folklore text as material for phonosemantic research in the light of reflection of synesthetic elements in it, its role is underlined as carrier of soundsymbolic information. It is made complex analysis of rhythmomelodic structure of 30 lullabies in German and Russian. As part of research it was marked a predominance of dimeters both in Russian and in German texts, in particular a trochaic, as well as consecutive use of anapestic metre in Russian lullabies with an expressions of threat, intimidation. Lexical-semantic analysis allowed distinguishing the groups, where there were identified the similarities and characteristic features taking in account national culture and traditions. The analysis did not identify synesthetic trope in Russian texts, but in German lullabies there were marked few single typical phrases. Key words: complex text analysis, phonosemantics, Russian and German folklore, lullabies, synesthesia. DOI 10.18522/1995-0640-2020-2-131-141